Kazakh traditional song and musical heritage of Abay (Música Hodie, 2024)
Kazakh traditional song culture has not been studied enough. For specialists and lovers of singing, the turning points of the song history are interesting, testifying to its qualitative renewal. These include the emergence of oral professionalism in song culture. The purpose of this article is a historical overview of the development of the Kazakh song, when the innovative songwriting of Abay, a poet and educator of the late 19th - early 20th century, spreads.The main problem in the study of traditional songs and songs of Abay is the definition of adequate cultural-historical (professionalism) and musical-stylistic approaches to analysis. Song creativity, recorded in musical and ethnographic collections (more than three thousand samples), collected in their own folklore expeditions and musical and concert practice of art carriers, was subjected to analysis. The methodology of studying Kazakh songwriting is based on the observation of folk music-making, musical and poetic analytics is based on the ratio of poetic text and melody, which determines the song genre. The method of data comparison and generalization allowed to determine the originality of different historical layers of the Kazakh traditional song. In the folk-professional song, the purposefulness of its development, the setting of artistic tasks is revealed. Abay's songwriting, being subject to his poetic reform, cannot follow the stylistic norms of the Kazakh oral-professional song.